Identification of Specific Gravity and Solubility in ethanol from citronella oil - Anwar Syahadat; Ayus Diningsih (Journal of Public Health and Pharmacy)
Introduction: Essential oil is also known as ethereal oil or flying oil (ethereal oil, volatile oil) produced by plants. The oil is volatile at room temperature without decomposition, has a bitter taste, smells good according to the smell of the plant that produces it, is generally soluble in organic solvents and insoluble in water. At high concentrations, essential oils can be used as local anesthetics, for example clove oil is used to treat toothaches, but can damage mucous membranes. Most essential oils also have strong antibacterial and antifungal properties.